Covid-Induced School Closures in the US and Germany: Long-Term Distributional Effects - Nicola Fuchs-Schündeln (Center for Economic Studies and ifo Institute (CESifo), 2022)
Almost all countries worldwide closed schools at the outbreak of the Covid-19 crisis. I document that schooling time dropped on average by -55% in the US and -45% in Germany from the onset of the crisis to the summer of 2021. In the US, schools were closed longer in richer than in poorer areas, while in Germany the regional variation is much smaller. However, Germany exhibited substantial variation by grade level, with a strong U-shaped patterns that implies that children attending middle school faced the longest closures. A structural model of human capital accumulation predicts that the US school closures on average lead to a reduction of life-time earnings of –1.7% for the affected children. While the overall losses are likely somewhat smaller in Germany, the socio-economic gradient in the losses could be larger than in the US, leading to increased inequality and decreased intergenerational mobility.
Keywords: E24; H75; I21; 330; Covid school closures; long-term effects